2011
DOI: 10.1002/jmri.23519
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted MRI of fatty liver

Abstract: Purpose: To investigate the effect of fat infiltration on the apparent diffusion coefficient (ADC) of liver, and assess the relationship between ADC and hepatic fat fraction (HFF).Materials and Methods: MRI scans of 120 consecutive patients were included in this retrospective study. Of these, 42 patients were included in the fatty liver group and 78 in the control group. ADC values were measured from a pair of diffusion-weighted (DW) images (b ¼ 0 mm 2 /s and 1000 mm 2 /s). HFFs were measured using T1W GRE dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 12 publications
4
44
5
Order By: Relevance
“…Our results demonstrated a significant decrease in the ADC value in the subgroups of patients with steatosis in both groups of patients with early and advanced fibrosis stages in comparison to that in patients without steatosis. Our results are in agreement with those reported by Poyraz et al (30), wherein it was reported that hepatic fat has an influence on the ADC value. The decrease in the ADC value observed in our study can be explained by hepatocyte swelling and the changes in the architectural structure of the liver that results from the accumulation of fat droplets in the liver cells (32).…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrated a significant decrease in the ADC value in the subgroups of patients with steatosis in both groups of patients with early and advanced fibrosis stages in comparison to that in patients without steatosis. Our results are in agreement with those reported by Poyraz et al (30), wherein it was reported that hepatic fat has an influence on the ADC value. The decrease in the ADC value observed in our study can be explained by hepatocyte swelling and the changes in the architectural structure of the liver that results from the accumulation of fat droplets in the liver cells (32).…”
Section: Discussionsupporting
confidence: 94%
“…In fact, a recent machine learning-based approach, combining MRI parameters derived from hepatic hemodynamic changes demonstrated strong correlations with hepatic fibrosis [38]. While the correlation of the combination of the biexponential model derived parameters and hepatic fibrosis did not exceed that achieved with the monoexponential model-derived diffusion coefficients, the multiple parameters derived with this approach may offer utility in mitigating confounding factors in deriving liver diffusion coefficients, such as the presence of hepatic steatosis, known to affect diffusion coefficients [39,40]. For instance, the presence of steatosis may preferentially affect one of the parameters obtained using a biexponential model.…”
Section: Discussionmentioning
confidence: 96%
“…One study in adults [18] and another in mice [19] found that ADC decreased with steatosis. Other studies in adults with NAFLD, however, demonstrated no significant relationship [15, 16, 36].…”
Section: Discussionmentioning
confidence: 99%